SOCRATE-PRODIGE 55 trial: A randomized phase II study to evaluate second-line ramucirumab alone or with paclitaxel in older patients with advanced gastric cancer. Issue 6 (June 2022) - Boisteau, Emeric; François, Eric; Aparicio, Thomas; Le Malicot, Karine; Boulahssass, Rabia; Lecomte, Thierry; Laurent-Puig, Pierre; Guiu, Boris; Paillaud, Elena; Galais, Marie-Pierre; Lopez-Trabada Ataz, Daniel; Tougeron, David; et al.
Abstract: Introduction: Patients ≥ 70 years old constitute 40% of patients with advanced gastric cancer (GC). Ramucirumab plus Paclitaxel is a therapeutic option validated in the second-line treatment of advanced GC, but as older patients are at higher risk of severe toxicity, due to comorbidities and/or frailty, we aimed to evaluate second-line Ramucirumab alone or combined with Paclitaxel in terms of overall survival (OS) and quality of life (QoL) in patients ≥ 70 years-old with advanced GC. Methods: In this multicenter, randomized, open-label, non-comparative, prospective phase II clinical trial, the main inclusion criteria are: patients ≥ 70 years old, with advanced GC having progressed after first-line chemotherapy or in the six months following the last administration of adjuvant chemotherapy, with WHO performance status <2. They are randomized to receive either ramucirumab alone (arm A) or ramucirumab plus Paclitaxel (arm B). The primary endpoint is 6-month OS and QoL evaluated with the EORTC QLQ-ELD14 questionnaire. The secondary endpoints include other parameters of QoL, time to definitive deterioration (TTDD) in QoL and TTDD in autonomy, treatment toxicities, other parameters of survival and disease control, identification of geriatric and nutritional prognostic scores and predictive factors of treatment safety and efficacy. OS of 60% is expected at 6 months (H0:40%). Using a Simon-minimax design, with one-sided α risk of 2% and 80% power for OS, and considering 5% lost to follow-up, it is necessary to randomize 56 patients in each arm. Perspectives: As older patients are at higher risk of chemotherapy toxicity, ramucirumab alone could be an interesting alternative to Paclitaxel plus ramucirumab, as a second-line therapy for patients ≥ 70 years old with advanced GC, and needs to be evaluated.